Influence of water intercalation and hydration on chemical decomposition and ion transport in methylammonium lead halide perovskites - Jong,UG; Yu,CJ; Ri,GC; McMahon,AP; Harrison,NM; Walsh,A (Journal of Materials Chemistry A, 2017)
The application of methylammonium (MA) lead halide perovskites, CH3NH3PbX3 (X = I, Br, Cl), in perovskite solar cells has made great recent progress in performance efficiency during recent years. However, the rapid decomposition of these materials in humid environments hinders outdoor application, and thus, a comprehensive understanding of the degradation mechanism is required. We investigate the effect of water intercalation and hydration of the decomposition and ion migration of CH3NH3PbX3 using first-principles calculations. We find that water interacts with PbX6 and MA through hydrogen bonding, and the former interaction increases gradually, while the latter hardly changes when going from X = I to Br and to Cl. Thermodynamic calculations indicate that water exothermically intercalates into the perovskite, and suggest that the water intercalated and monohydrated compounds are stable with respect to decomposition. More importantly, the water intercalation reduces the activation energies for vacancy-mediated ion migration, which become higher going from X = I to Br and to Cl. Our work indicates that hydration of halide perovskites must be avoided to prevent the degradation of solar cells upon moisture exposure.